Auditoría de gestión al proceso de compras públicas de la Empresa Pública Municipal de Agua Potable y Alcantarillado de San Miguel de Bolívar”, año 2021 - Mora Quintana, Paola Vanessa (2023)
This research was developed under the objective of developing a management audit for the evaluation of the level of compliance of effectiveness and efficiency in the public procurement process in the Municipal Public Company of Drinking Water and Sewerage of San Miguel de Bolivar, year 2021, being necessary for it the use of a methodology based on the mixed approach, that is to say that encompasses the qualitative and quantitative paradigms, which allowed the application of research instruments such as the survey and the interview, This provided a clear idea about the development of internal control in the organization, with which it was possible to detect among the main results that there is a low level of knowledge about the public procurement process by the staff, being one of the causes the fact that this function is not defined in the manual of functions as well as the fact that there is an overload of work due to the lack of staff in the financial area. For this reason, a management audit of the organization was carried out, which showed that there were some shortcomings such as the disorganization of the physical file, unfoiled sheets, payments to suppliers out of time, among others. Finally, it was highlighted the fact that training on this process has not been developed frequently and to all staff, which is reflected in the results obtained from the audit. Key words: performance audit, public procurement process, internal control, level of compliance.